THE EFFECT OF INTERNAL LOCUS OF CONTROL, VILLAGE APPARATUS COMPETENCE, AND SELF-EFFICACY ON THE PREVENTION OF VILLAGE FUND FRAUD - Ni Made Putri Ari Utarini; Ni Luh Supadmi (CV. ADIBA AISHA AMIRA, 2026)
The prevention of Village Fund fraud has become a crucial issue due to the increasing allocation of Village Funds and the high number of irregularities in their management. Fraud prevention efforts can be carried out by strengthening internal factors and the competence of village officials. This study aims to empirically examine the effect of internal locus of control, village apparatus competence, and self-efficacy on the prevention of Village Fund fraud. The research was conducted in Badung Regency, Bali Province, involving village officials from 46 villages using a purposive sampling technique, including village heads, secretaries, and treasurers who had served for at least one year. The collected data were analyzed using multiple linear regression analysis. The results indicate that internal locus of control, village apparatus competence, and self-efficacy have a positive and significant effect on the prevention of Village Fund fraud. This implies that improvements in internal locus of control, village apparatus competence, and self-efficacy can enhance fraud prevention in Village Fund management.